The reality of privatization of education in terms of needs and quality of education: Arab private schools in the Galilee region as a model (The International Journal for Scientific Research, 2024)
The study aimed to identify the reality of privatization of education in terms of needs and quality of education in Arab private schools in the Galilee region. The study relied on the descriptive analytical approach. The questionnaire was applied to the study sample members, numbering (304) teachers and (629) parents, who were selected using the stratified random cluster method. The study reached the following results: The arithmetic averages showed that the most important educational needs that private schools can meet are providing a good educational environment, and the level of quality of education in private schools was high. The results also showed that the private school has a good reputation, and the school principal has high administrative experience and a competent teaching staff. The results also showed that there are no statistically significant differences between the study sample members regarding the reality of privatization of public education in Arab schools, which can be attributed to the social status and monthly income of the family. While it showed the existence of statistically significant differences related to the educational level. The study recommended the necessity of establishing programs to enhance cooperation between private schools and government schools with the aim of improving Arab education.
Keywords: Private schools; quality of education; Arab society